The influence of catchment scale on comprehensive heat transfer performance about tube fin heat exchanger in numerical calculation - Hongtao Li; Shuai Zhang; Yunguang Ji; Mingxu Sun; Xudong Li; Yonggang Sheng (Energy Reports, 2022)
The purpose of enhanced heat exchange technology is to improve the heat exchange performance of heat exchange equipment, but the increase of resistance causes the decrease of energy consumption and economic benefits. Then the comprehensive evaluation index is used to evaluate the comprehensive heat exchange performance of heat exchange equipment. In the process of numerical simulation, there is no unified standard for the value of the catchment scale. In this paper, by changing the length of the entrance and exit of the external passage of the tube-fin heat exchanger, the change law of comprehensive heat transfer performance index (j⋅f−1/3) for heat exchanger at different Reynolds numbers was studied by numerical simulation. The results show that the heat transfer effect is better than that without extension, and the effect is the best when it is 1.5 times, and the growth rate is more than 1.5%; compared with the non extended conditions, the extended outlet basin has little impact, and the maximum increase of c comprehensive heat transfer performance index (j⋅f−1/3) is no more than 0.75%. Therefore, in the numerical simulation, the inlet of the external basin of the heat exchanger can be extended by 1.5 times of the base tube diameter, and the outlet is not extended.